Thoracic Limb Osteosarcoma in a Dog: Treatment with Endo-Exo-Prosthesis - Martins Araújo, Iara; Augusto Lopes Muzzi, Leonardo; Munhoz, Daniel; Athanasio, Raquel; Costa Mancilha Dias, Luana; Pimenta Neves, Mariana; de Souza Pereira, Lucas; Meira Liberato, Ivy (Acta Scientiae Veterinariae, 2026)
Background: Osteosarcoma (OSA) is the most common primary malignant bone tumor in dogs, accounting for approximately 85% of all malignant bone neoplasms. It primarily affects large-breed and older dogs, with the appendicular skeleton being the most affected site. The disease has an aggressive course, a high metastatic rate, and usually a poor prognosis. Treatment generally involves surgery and chemotherapy, with limb amputation being the traditional procedure. The study aims to report the case of a Saint Bernard dog with OSA in the distal region of the radius and ulna, treated with surgical partial limb amputation and implantation of an endo-exo-prosthesis, and adjuvant chemotherapy. Case: A 9-year-old, intact male Saint Bernard dog, weighing 65 kg, was admitted to the University Veterinary Hospital with a history of swelling in the distal region of radius and ulna of the left thoracic limb. Radiographic and histopathological evaluation confirmed a diagnosis of osteosarcoma (OSA), and staging examinations showed no evidence of pulmonary metastases. The treatment included partial limb amputation at the mid-third of the radius and ulna followed by implantation of a custom-made titanium endo-exo-prosthesis, and adjunctive chemotherapy. The surgical procedure involved osteotomy of the radius and ulna, intramedullary canal reaming for implant accommodation, and manual implantation of the endo-exo-prosthesis. Immediate postoperative radiographic assessment indicated proper implant positioning. Five days after surgery, soft tissue retraction and suture dehiscence occurred, leading to bone exposure and requiring soft tissue reapproximation at the base of the prosthesis. After 20 days of hospitalization, the patient was discharged with incomplete healing at the skin-implant interface, requiring continuous home wound care. Upon returning 45 days after surgical procedure, the patient showed signs of implant infection. Radiographic examination revealed peri-implant bone resorption and irregular bone proliferation. Bacterial culture identified Klebsiella pneumoniae strain, sensitive to meropenem. After completion of antibiotic therapy, a subsequent culture identified a multidrug-resistant Acinetobacter sp. infection. Given the ongoing infection and progressive peri-implant bone resorption and implant failure, limb amputation was performed approximately three months after prosthesis implantation. Approximately 6 months after the OSA diagnosis, the patient was hospitalized with severe dyspnea. Thoracic radiography revealed the presence of pulmonary metastases, and euthanasia was performed. Discussion: The use of endo-exo-prosthesis in dogs presents significant challenges, particularly concerning the soft tissue–implant interface and osseointegration. Successful adaptation of the skin and musculature to the prosthesis is critical for long-term outcomes, as failures at this interface can lead to complications such as infection, dehiscence, and implant failure. Canine patients pose additional difficulties due to factors such as the presence of fur, considerable variability in limb anatomy and size, challenges in enforcing activity restriction, and the potential for secondary issues caused by licking behavior. The reported case highlights both the potential benefits and challenges of endo-exo-prostheses in the treatment of canine OSA. Although the procedure initially preserved limb functionality, postoperative complications, such as soft tissue retraction, infection, and issues with osteointegration, resulted in prosthetic implant failure. The need for improved surgical techniques and the development of technologies that enhance osteointegration and healing at the skin-implant interface is emphasized, aiming to reduce complication rates and improve patient outcomes. Keywords: bone neoplasm, limb amputation, prosthesis, chemotherapy. Título: Osteossarcoma de membro torácico em um cão: tratamento com endo-exo-prótese Descritores: neoplasia óssea, amputação de membro, prótese, quimioterapia.